Comparative Investigation of Copper Tolerance and Identification of Putative Tolerance Related Genes in Tardigrades - Hygum, Thomas L.; Fobian, Dannie; Kamilari, Maria; Jørgensen, Aslak; Schiøtt, Morten; Grosell, Martin; Møbjerg, Nadja (Frontiers in Physiology, 2017)
Tardigrades are microscopic aquatic animals renowned for their tolerance towards extreme environmental conditions. The current study is the first to investigate their tolerance towards heavy metals and we present a novel tardigrade toxicant tolerance assay based on activity assessments as a measure of survival. Specifically, we compare tolerance towards copper in four species representing different evolutionary lineages, habitats and adaptation strategies, i.e. a marine heterotardigrade, Echiniscoides sigismundi, a limno-terrestrial heterotardigrade, Echiniscus testudo, a limno-terrestrial eutardigrade, Ramazzottius oberhaeuseri and a marine eutardigrade, Halobiotus crispae. The latter was sampled at a time of year, when the population is predominantly represented by aberrant P1 cysts, while the other species were in normal active states prior to exposure. Based on volume measurements and a general relation between body mass and copper tolerance, expected tardigrade EC50 values were estimated at 0.5-2 µg l-1. Following 24 hours of exposure, tolerance was high with no apparent link to lineage or habitat. EC50s (95% CI), 24 hours after exposure, were estimated at 178 (168-186) and 310 (295-328) μg l-1, respectively, for E. sigismundi and R. oberhaeuseri, whereas E. testudo and H. crispae were less affected. Highest tolerance was observed in H. crispae with a mean±s.e.m. activity of 77±2% (n=3) 24 hours after removal from approximately 3 mg l-1 copper, suggesting that tardigrade cysts have increased tolerance towards toxicants. In order to identify putative tolerance related genes, an E. sigismundi transcriptome was generated and searched for key enzymes involved in osmoregulation, antioxidant defense and copper metabolism. We found high expression of Na/K ATPase and carbonic anhydrase, known targets for copper. Our transcriptome, furthermore, revealed high expression of antioxidant enzymes, copper transporters, ATOX1 and a Cu-ATPase. In summary, our results indicate that tardigrades express well-known key osmoregulatory enzymes, supporting the hypothesis that copper inhibits sodium turnover as demonstrated for other aquatic organisms. Tardigrades, nevertheless, have high tolerance towards the toxicant, which is likely linked to high expression of antioxidant enzymes and an ability to enter dormant states. Tardigrades, furthermore, seem to have a well-developed battery of cuproproteins involved in copper homeostasis, providing basis for active copper sequestering and excretion.